Perancangan Balance Scorecard untuk Mengembangkan Modal Insani dan Meningkatkan Kinerja pada Usaha Kecil dan Menengah (UKM) - Erwina, .; Sukmawati, Anggraini; Sumertajaya, I Made (Jurnal Aplikasi Manajemen, 2015)
The success of SMEs could be seen from their performance. However, until now theperformance measurement still use the traditional way in which views the performance onlyfrom the financial perspective. Therefore, it needs a new performance measurement systemwhich is balance scorecard. Based on the problems, this study aimed at designing a performancemeasurement in SMEs with balance scorecard approach as an attempt to develop thehuman capital and to improve the SMEs'performance. The study was conducted in BogorSMEs. The sampling technique was carried out using purposive sampling. The samples ofthis study were SMEs owner, related official, and the expert of SMEs and BSC. The datatabulation and analysis were used literature study, focus group discussion, and in-depthinterview. The result of the study formulated eight strategic targets from four perspectivesand 15 key performance indicators to measure performance in SMEs.